Protective role of dexmedetomidine against sevoflurane-induced postoperative cognitive dysfunction via the microRNA-129/TLR4 axis. (October 2021) - Wei, Wei; Sun, Zhentao; He, Shifeng; Zhang, Wanyue; Chen, Sai
Highlights: Dex treatment promotes behavioral cognition and neuronal activity in POCD rats. Dex increases miR-129 expression in hippocampus and cortical neurons. miR-129 antagomir attenuates the neuroprotective effect of Dex on POCD rats. miR-129 targets TLR4. TLR4 activates the NF-KB pathway to promote neuronal damage after POCD in rats. Abstract: The involvement of Dexmedetomidine (Dex) has been indicated in postoperative cognitive dysfunction (POCD), while the mechanism is not well characterized. This study estimated the mechanism of Dex in POCD. Rats were anesthetized with sevoflurane (SEV) to evoke POCD and then subjected to Morris water maze test to detect the cognitive and behavioral function. Then, the damage of hippocampus and cortex, and apoptosis and activity of neurons were examined. Microarray analysis was performed to screen out the differentially expressed microRNAs (miRs) in rats after Dex treatment. The cognitive and behavioral functions and neuronal activity of rats were detected after miR-129 antagomir injection. The target of miR-129 was predicted. The levels of TLR4 and NF-κB p65 in hippocampus and cortex were measured. Dex treatment alleviated SEV-induced behavior and cognitive impairments in rats, promoted neuronal activity and hindered neuronal apoptosis. After treatment with Dex, miR-129 expression was elevated in brain tissues, and the neuroprotection of Dex on POCD rats was partially annulled after injection of miR-129 antagomir. Furthermore, miR-129 targeted TLR4 and prevented the phosphorylation of NF-κB p65. In summary, Dex ameliorated SEV-induced POCD by elevating miR-129 and inhibiting TLR4 and NF-κB p65 phosphorylation. This study may shed new lights on POCD treatment.